Becoming a Vehicle of Knowledge Creation: How Autopoiesis Changed My Practice - Rød, Anne (Murmurations: Journal of Transformative Systemic Practice, 2024)
Autoethnographic narratives are ways of normalising and giving meaning to the human experience, allowing the reader to resonate with what is relevant and important in the writer’s experience, while generating new insights and knowledge we would not otherwise access. Using my doctoral journey of striking moments and the shifts created in me, in this paper, I argue that human experiences must be valued as equal to diagnostic and objectivist approaches in the pursuit of knowledge. By juxtaposing my autoethnographic narrative with the Theory of Autopoiesis, acting as both a framework of analysis and metaphor, I offer my emotional process as a political representation, a questioning of power paradigms and a source of knowledge and support to other researchers. The rendering of my journey, from working in and believing in organisations governed by a business logic and rational economic theory, to daring to challenge such discursive powers, shows what is possible through conscious noticing, embracing, and transformation. I argue that by combining scientific theories with analytical autoethnography, we can bridge sciences and communities of practice, and open doors for the application of autoethnography in new professional domains, thereby significantly contributing to an adjustment of research practices and to what counts as knowledge.